2019
DOI: 10.1002/ppsc.201900058
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Multifunctional Gold Decorated Dendritic Mesoporous Silica/Tantalum Oxide Nanoparticles for Intraperitoneal Tumor‐Specific Delivery

Abstract: Nonspecific high‐energy radiation for treatment of metastatic ovarian cancer is limited by damage to healthy organs, which can be mitigated by the use of radiosensitizers and image‐guided radiotherapy. Gold (Au) and tantalum oxide (TaOx) nanoparticles (NPs), by virtue of their high atomic numbers, find utility in the design of bimetallic NP systems capable of high‐contrast computed tomography (CT) imaging as well as a potential radiosensitizing effect. These two radio‐dense metals are integrated into dendritic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Recently, Kashfi-Sadabad et al reported a class of dendritic mesoporous silica/tantalum oxide nanoparticles adorned with gold for the treatment of metastatic ovarian cancer. 74 It is worth noting that the porous structure of the as-synthesized TaO x nanoparticles enabled the effective loading of radio-dense elements as imaging-guided radiotherapeutic nanoagents, leading to strong X-ray contrast enhancement and specific tumor targeting. Apart from tantalum-based contrast nanoagents, there are few reports about W-based contrast agents, because of their organ toxicity and environmental pollution issues.…”
Section: ■ Contrast Nanoagents For X-ray Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Kashfi-Sadabad et al reported a class of dendritic mesoporous silica/tantalum oxide nanoparticles adorned with gold for the treatment of metastatic ovarian cancer. 74 It is worth noting that the porous structure of the as-synthesized TaO x nanoparticles enabled the effective loading of radio-dense elements as imaging-guided radiotherapeutic nanoagents, leading to strong X-ray contrast enhancement and specific tumor targeting. Apart from tantalum-based contrast nanoagents, there are few reports about W-based contrast agents, because of their organ toxicity and environmental pollution issues.…”
Section: ■ Contrast Nanoagents For X-ray Imagingmentioning
confidence: 99%
“…Various modifications on the surface of the nanoparticles were performed to improve the biological properties of TaO x . Recently, Kashfi-Sadabad et al reported a class of dendritic mesoporous silica/tantalum oxide nanoparticles adorned with gold for the treatment of metastatic ovarian cancer . It is worth noting that the porous structure of the as-synthesized TaO x nanoparticles enabled the effective loading of radio-dense elements as imaging-guided radiotherapeutic nanoagents, leading to strong X-ray contrast enhancement and specific tumor targeting.…”
Section: Contrast Nanoagents For X-ray Imagingmentioning
confidence: 99%
“…[32] The employment of PEG on the surface of these nanocapsules was due to its potential in prolonging circulation half-life, as well as to provide similar surface chemistry when compared with other nanomedicines of interest (e.g., Doxil and Doxoves; PEGylated liposomal doxorubicin), considering the importance of surface chemistry on mass transport mechanisms associated with nanoparticle deliverability to tumors. Evidently, the use of radio-opaque nanoparticles for X-ray CT imaging has been explored before, mainly focusing on metalbased nanostructures due to their high X-ray attenuation, [47][48][49][50][51] or nanostructures encapsulating small-molecule iodinated (SMI) contrasts (e.g., iohexol, iopamidol). [52,53] With the purpose of employing radio-opaque nanoparticles as imaging probes for nanoparticle deliverability assessments, the PFOB NC system developed by our group displays greater potential as it combines a variety of characteristic: 1) their relevant particle size distribution when compared with commercial nanomedicines of interest (within 100-300 nm distribution range); 2) similar surface chemistry due to PEGylation conferred by the PEG-b-PCL(Ch) copolymer; 3) PFOB load easily tunable to a maximum of 40% v/v, [32] enhancing X-ray attenuation; and 4) high nanoparticleto-signal correlation as PFOB is a structural component of NC and it is unlikely to leak out, as observed for SMI contrast-loaded nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, folate-receptor targeting nanoparticles in the form of self-assembling biopolymer (100 nm) and dendrimer (5 nm) nanoparticles have been recently developed for ovarian cancer applications; however, they have yet to be studied in orthotopic tumor models [ 169 , 170 ]. Similarly for CT, nanoparticles devised of tantalum, mesoporous silica and surface attached gold nanoparticles, 166 nm in size, have demonstrated excellent CT contrast in a peritoneal tumor after intraperitoneal injection [ 171 ]. The encapsulation of perfluorooctyl bromide (an existing CT contrast agent) in targeted polymers nanoparticles has also been shown to be a potential CT molecular imaging agent in ovarian xenograft subcutaneous models [ 172 ].…”
Section: Recent Developments Of Nanoparticles For Ovarian Cancer Diagnosticsmentioning
confidence: 99%